High Sensitivity Terahertz Biosensor Based on Goos-Hänchen Effect in Graphene - Jiang-Yu Liu; Tie-Jun Huang; Li-Zheng Yin; Feng-Yuan Han; Pu-Kun Liu (IEEE Photonics Journal, 2020)
Terahertz biosensing provides a suitable method to identify biomolecules due to their rich spectral fingerprint in this electromagnetic region. However, owing to the limitations of terahertz sources and detectors, the signal is weak and requires to be enhanced by particular technologies. In this paper, we propose a terahertz plasmonic biosensor based on Goos-Hänchen effect in graphene. Sample sensing can be realized by measuring the Goos-Hänchen shift of the reflected light. Numerical simulations show that the sensitivity of this biosensor can reach a high value up to $2.5× 10^4μ$ m/RIU. This graphene plasmonic configuration combined with Goos-Hänchen effect provides a novel high-sensitivity approach for future terahertz biosensing applications.